Auxin Biosynthesis in Maize Kernels - Glawischnig, Erich (American Society of Plant Physiologists, 2000)
Auxin biosynthesis was analyzed in a maize (Zea mays) kernel culture system in which the seeds develop under physiological conditions similar to the in vivo situation. This system was modified for precursor feeding experiments. Tryptophan (Trp) is efficiently incorporated into indole-3-acetic acid (IAA) with retention of the 3,3′ bond. Conversion of Trp to IAA is not competed by indole. Labeling with the general precursors [U-(13)C(6)]glucose and [1,2-(13)C(2)]acetate followed by retrobiosynthetic analysis strongly suggest that Trp-dependent IAA synthesis is the predominant route for auxin biosynthesis in the maize kernel. The synthesis of IAA from indole glycerol phosphate and IAA formation via condensation of indole with an acetyl-coenzyme A or phosphoenolpyruvate derived metabolite can be excluded.